Comparative matters : the renaissance of comparative constitutional law - Hirschl, Ran (Oxford : Oxford University Press, 2014)
Charting the history and analytical underpinnings of comparative constitutional inquiry, this book probes the various types, aims, and methodologies of engagement with the constitutive laws of others through the ages. It explores how and why comparative constitutional inquiry has been and ought to be pursued by academics and jurists worldwide.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 2, 2014).
Keywords: Constitutional law; Comparative law; Law; Laws of specific jurisdictions & specific areas of law